2020
DOI: 10.1177/2347631120970757
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Laboratory: A Boon to the Mechanical Engineering Education During Covid-19 Pandemic

Abstract: The engineering students understand the engineering concepts effectively when they conduct the experiments in the laboratory. Hence, laboratory is as important as theory; however, the ill-equipped laboratory facilities affect the students’ learnability. The virtual laboratories may help the students overcome the problems faced by them in the conventional laboratory. In India, educational activities during the middle of the semester were affected due to lockdown related to COVID-19. However, the theory classes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
50
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 21 publications
2
50
0
11
Order By: Relevance
“…While the theory classes were conducted online, the educational institutions found it difficult to complete the syllabus concerning the laboratory experiments due to the closure of universities as well as conventional laboratories. Kapilan et al [74] presented the exploitation of virtual laboratories based on simulation during the COVID-19 pandemic for providing learners of mechanical engineering education the opportunity to complete the planned laboratory experiments; the learners' feedback in this study indicated that the virtual laboratories helped them to understand the theoretical concepts, and they felt that it was necessary to introduce virtual laboratories into the engineering curriculum. García-Vela et al's study [75] recommended maintaining the use of the virtual spaces developed during the pandemic as a resource to reinforce the teaching and learning process.…”
mentioning
confidence: 78%
“…While the theory classes were conducted online, the educational institutions found it difficult to complete the syllabus concerning the laboratory experiments due to the closure of universities as well as conventional laboratories. Kapilan et al [74] presented the exploitation of virtual laboratories based on simulation during the COVID-19 pandemic for providing learners of mechanical engineering education the opportunity to complete the planned laboratory experiments; the learners' feedback in this study indicated that the virtual laboratories helped them to understand the theoretical concepts, and they felt that it was necessary to introduce virtual laboratories into the engineering curriculum. García-Vela et al's study [75] recommended maintaining the use of the virtual spaces developed during the pandemic as a resource to reinforce the teaching and learning process.…”
mentioning
confidence: 78%
“…Then videos on real laboratory experiments had also been shared for the comparison of virtual and real experimental results. Finally, a questionnaire had been provided to the students to obtain feedback (Kapilan et al, 2021). The majority of the faculty members had denoted that they have improved in terms of knowledge and skills.…”
Section: Laboratory Activities Through Virtual Laboratory Platforms and Techniquesmentioning
confidence: 99%
“…Further, as the study shows the students are comfortable in participating in the virtual labs, where a few students had mentioned that they had network connectivity issues in participating the virtual labs. Moreover, as Figure 5 shows more than half of the students had selected that quality of learning increases from the virtual labs and virtual labs needs to be introduced into the curriculum also (Kapilan et al, 2021). According to Figure 5, the majority (77%) of students had selected that they require virtual labs for the higher semesters also.…”
Section: Laboratory Activities Through Virtual Laboratory Platforms and Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Then videos on real laboratory experiments had also been shared for the comparison of virtual and real experimental results. Finally, a questionnaire had been provided to the students to obtain feedback (Kapilan et al, 2021).…”
Section: Laboratory Activities Through Virtual Laboratory Platforms and Techniquesmentioning
confidence: 99%